PERLINDUNGAN HUKUM TERHADAP EMERGENCY CONTACT DALAM PINJAMAN ONLINE PEER TO PEER LENDING - Okisari, Irma Nurul; Pranoto, Pranoto (Fakultas Hukum Universitas Sebelas Maret, 2025)
This article aims to examine the legal protection of Emergency Contacts in online credit transactions. This research is a normative legal research with a perspective which using primary and secondary legal materials. The data collection technique which is used in this study is an act and case approach. Data analysis in this study used systematic, grammatical and historical techniques. The legal problem that arises is how debt collector collect the debt when debt payment failure happened in online credit transactions carried out by debtors. Sometimes, billing method which is used are using harsh words even with intimidation, so that affecting Emergency Contacts. The problem solution of emergency contacts needs to be provided with legal protection both externally and internally